Associations Among Work-Related and Leisure-Time Physical Activity With Level of Nausea During Pregnancy. Issue 4 (July 2019) - Connolly, Christopher P.; Mudd, Lanay M.; Pivarnik, James M.
Objective: Pregnancy-induced nausea and vomiting are common maladies during early pregnancy and may be related to physical activity (PA). Our objective was to determine relations among work-related PA (work PA), leisure-time physical activity (LTPA), and nausea during the first trimester. Study design: Online or mailed surveys with questions on pregnancy-related nausea, work PA, and LTPA were completed by 70 women at 15 to 30 months postpartum. Women recalled nausea during the first trimester (none, ≤1 h/d, 2-3 h/d, 4-6 h/d, ≥6 h/d) as well as LTPA frequency, duration, and type. Women also recalled total working hours in their first trimester and percentage of time sitting, standing, and walking at work. Results: A total of 42 women (60%) were categorized as having high nausea (≥2 h/d). Mann-Whitney U tests showed that women with low nausea had significantly more MET minutes per week of LTPA (P = .05) and hours per week spent standing at work (P = .03). Logistic regression analyses showed standing for ≥20 h/wk at work was related to reduced odds of high nausea (adjusted odds ratio = 0.23; 95% CI = 0.06-0.96), whereas meeting LTPA guidelines was nonsignificantly related to reduced odds. Conclusion: These findings suggest an inverse relationship between first trimester PA and level of nausea. Further investigation is needed to determine the directionality of these relations.